REPRESENTASI KORUPSI DALAM NASKAH DRAMA TUYUL KARYA ARIF KHILWA SEBUAH PERSPEKTIF ALAN SWINGEWOOD - filawatifila, filawatifila; Diana, Ririn Sefty; Talib, Arianti (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2025)
This study aims to describe the representation of corruption in the play Tuyul by Arif Khilwa using Alan Swingewood’s approach to the Sociology of Literature. The method employed is descriptive-interpretative. The data consist of excerpts from dialogues, narratives, or scenes that portray corruption within the play. Data collection was carried out through literature review, close reading, and note-taking techniques. The data were analyzed using an interpretative analysis method. The findings reveal that the corruption depicted in Tuyul exists at the level of political corruption, characterized by individual moral deviation within a rationalized social system. Through the character of Karlan, the play illustrates the power imbalance between political elites and the general public. This behavior represents the capacity of individuals to adapt to a corrupt social structure as a means of survival. Individual involvement in a corrupt system is shown not merely as a personal choice, but as the outcome of socialization processes that normalize deviant practices in society. In the socio-political context of Indonesia, this play serves as a form of social critique that exposes the darker aspects of society, particularly the relationship between power, personal interests, and the interests of specific groups. The lack of effective public accountability creates opportunities for the abuse of power, thereby fostering the proliferation of corrupt practices. Thus, the play stands as a symbolic act of resistance against corruption.